Virtual Reality in the Assessment, Understanding and Treatment of Mental Health Disorders - Riva, Giuseppe; Serino, Silvia (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
In the computer sciences, virtual reality (VR) is usually described as a set of fancy technologies. However, in medicine and neuroscience, VR is instead defined as an advanced form of human-computer interface that allows the user to interact with and become present in a computer-generated environment. The sense of presence offered by VR makes it a powerful tool for personal change because it offers a world where the individual can stay and live a specific experience. For this reason, the use of VR in mental health shows promise: different types of research support its clinical efficacy for conditions including anxiety disorders, stress-related disorders, obesity and eating disorders, pain management, addiction, and schizophrenia. However, more research is needed to transform VR according to a clinical standard for mental health. This Special Issue aims to present the most recent advances in the mental health applications of VR, as well as their implications for future patient care.